Optimal mobile beacon trajectories for nodes localisation in wireless sensor networks. (2018) - Benkouider, Sara; Lagraa, Nasreddine; Yagoubi, Mohamed Bachir; Benslimane, Abderrahim
The random deployment of nodes is commonly used in wireless sensor networks (WSNs), because of either the hostility of the monitored area or its large scale. However, many applications and protocols are position-based. Hence, it's necessary to determine the position of sensors even after their deployment. Localisation techniques using mobile beacon have been proposed in this context, to localise unknown sensor nodes. However, to save nodes energy it's useful to send an optimal number of messages. Thus, an optimal trajectory of mobile beacon helps to achieve such objective. In this paper, we propose two novel optimal mobile beacon trajectories based on Hilbert curve. The first proposal aims at minimising the trajectory length and improving the localisation accuracy, moreover, the second one minimises both the trajectory and the energy consumption. In this study, we compare the proposed techniques with mobile Hilbert beacon trajectory. The analytical analysis and the performance evaluation with simulations show that our proposed methods improve, compared to the existing methods, the accuracy, the length of trajectories and the energy consumption.